2024
DOI: 10.1002/ange.202319913
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Structure‐Activity Relationship Towards CO2 Electroreduction over SnO2 by A Standard Research Paradigm

Zhongyuan Guo,
Yihong Yu,
Congcong Li
et al.

Abstract: Authentic surface structures under reaction conditions determine the activity and selectivity of electrocatalysts, therefore, the knowledge of the structure−activity relationship can facilitate the design of efficient catalyst structures for specific reactivity requirements. However, understanding the relationship between a more realistic active surface and its performance is challenging due to the complicated interface microenvironment in electrocatalysis. Herein, we proposed a standard research paradigm to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
1
0
0
Order By: Relevance
“…Li et al found that the formation of the metallic surface with abundant oxygen vacancies over the Cu oxide catalysts is the key to the high C–C coupling performance in CO 2 reduction reaction (CO 2 RR). Recently, a similar conclusion was found by Guo et al on SnO x for CO 2 RR, by combining surface Pourbaix analysis and subsequent structural evolution and activity analysis. Yang et al identified the dual-atom catalysts’ bridge-site poisoning effect of CO* during the CO 2 RR and HO*/O* during the ORR and oxygen evolution reaction.…”
Section: Introductionsupporting
confidence: 80%
“…Li et al found that the formation of the metallic surface with abundant oxygen vacancies over the Cu oxide catalysts is the key to the high C–C coupling performance in CO 2 reduction reaction (CO 2 RR). Recently, a similar conclusion was found by Guo et al on SnO x for CO 2 RR, by combining surface Pourbaix analysis and subsequent structural evolution and activity analysis. Yang et al identified the dual-atom catalysts’ bridge-site poisoning effect of CO* during the CO 2 RR and HO*/O* during the ORR and oxygen evolution reaction.…”
Section: Introductionsupporting
confidence: 80%